2004
DOI: 10.1029/2004ja010583
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variability of equatorial plasma bubbles observed by DMSP and ROCSAT‐1

Abstract: [1] We compare observations of equatorial plasma bubbles (EPBs) by polar-orbiting satellites of the Defense Meteorological Satellite Program (DMSP) with plasma density measurements from the Republic of China Satellite (ROCSAT-1) in a low-inclination orbit. DMSP data were acquired in the evening sector at low magnetic latitudes between 1989 and 2002. ROCSAT-1 plasma densities were measured in March and April of 2000 and 2002. Observations of individual EPBs detected by both ROCSAT-1 and DMSP were well correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
344
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(408 citation statements)
references
References 38 publications
60
344
3
1
Order By: Relevance
“…As the GPS signal loss at low latitudes is caused by the EPIs, similar seasonal dependences are expected from them, e.g., higher occurrence around equinoxes and December solstice months from a global view (Burke et al, 2004;Su et al, 2006;Stolle et al, 2008;Xiong et al, 2010). However, the seasonal dependence of polar patches is still an open issue: some studies reported that the polar patches are mainly a local winter phenomenon in both hemispheres (e.g., Coley and Heelis, 1998;Kivanç and Heelis, 1998;Carlson, 2012;Spicher et al, 2017), while there are also studies found that polar patches have higher occurrence during December solstice months in both hemispheres (e.g., Noja et al, 2013;Chartier et al, 2018).…”
Section: Seasonal Dependence Of Gps Signal Lossmentioning
confidence: 63%
“…As the GPS signal loss at low latitudes is caused by the EPIs, similar seasonal dependences are expected from them, e.g., higher occurrence around equinoxes and December solstice months from a global view (Burke et al, 2004;Su et al, 2006;Stolle et al, 2008;Xiong et al, 2010). However, the seasonal dependence of polar patches is still an open issue: some studies reported that the polar patches are mainly a local winter phenomenon in both hemispheres (e.g., Coley and Heelis, 1998;Kivanç and Heelis, 1998;Carlson, 2012;Spicher et al, 2017), while there are also studies found that polar patches have higher occurrence during December solstice months in both hemispheres (e.g., Noja et al, 2013;Chartier et al, 2018).…”
Section: Seasonal Dependence Of Gps Signal Lossmentioning
confidence: 63%
“…Simultaneous sunset is expected to intensify the so-called PRE (Abdu et al, 1981(Abdu et al, , 1992(Abdu et al, , 2010Batista et al, 1986), a favorable and sufficient condition for the initiation of RTI. The angle between the geomagnetic meridian and the sunset terminator line was introduced as a proxy of the simultaneous sunset in the conjugate points (Burke et al, 2004). Since, in the Brazilian longitude sector, the angle tends to be much closer during NovemberFebruary than March-September, higher occurrence probabilities and greater S 4max are more expected during the November-February (see Figs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…There have been many studies on the occurrence characteristics of ionospheric density irregularities using groundbased measurements (Rastogi, 1980;Abdu, 2001), satellitebased in situ measurements (Watanabe and Oya, 1986;Huang et al, 2002;Burke et al, 2004), and topside sounders (Maruyama and Matuura, 1984), and many important features of these have been reported including temporal variations (Sahai et al, 2000;Huang et al, 2002), seasonallongitudinal variability (Burke et al, 2004), several-day variation, and day-to-day variation (Basu et al, 1996) though several enigmatic features of them are yet to be revealed (Thampi et al, 2009). However, studies on continuous and global characteristic features of ionospheric plasma irregularities are very scanty due to the fact that the global coverage is difficult to obtain from ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…2.1, the eastward daytime equatorial electric field sometimes shows a significant increase before it reverses to the nighttime westward direction. The strong eastward equatorial electric field during the pre-reversal enhancement is linked to another phenomena called equatorial spread-F or plasma bubble, which is characterized by a depletion of the equatorial ionospheric plasma density (e.g., Burke et al 2004;Stolle et al 2006). Attempts have been made by several authors (e.g., Sreeja et al 2009;Uemoto et al 2010;Hajra et al 2012) to find a link between geomagnetic daily variations and the occurrence of the equatorial spread-F. For example, Uemoto et al (2010) reported that the occurrence of the equatorial spread-F is reduced when the equatorial electrojet 1-2 hours prior to the sunset is westward.…”
Section: Eej Intensity and Equatorial F-region Parametersmentioning
confidence: 99%